Preliminary CFD investigation for secondary coolant in molten salt reactor with alumina nanofluid considering FLiBe and FLiNaK as base fluid through a double pipe heat exchanger (Journal of Bangladesh Academy of Sciences, 2022)
This work analyzes a computational fluid dynamics (CFD) methodology based on ANSYS to investigate the 3 % and 4 % volume fraction alumina (Al2O3) nanofluids with base fluids FLiBe (LiF(67)-BeF2(33) (mol%)) and FLiNaK (LiF(46.5)-NaF(11.5)-KF(42) (mol%) through a double pipe heat exchanger. The purpose of the paper is to choose better candidates as secondary coolants in molten salt reactors for better thermodynamics performances and heat transfer characteristics. Six secondary coolants with and without nanofluids and fuel salt as primary coolants are driven through the inner and outer pipe. Later overall heat transfer coefficient, outlet temperatures and pressure drops of the fluids, and LMTD are calculated. Thus, this work eventually recommends the best candidate as a secondary coolant by CFD methodology using ANSYS-FLUENT 18.1.J. Bangladesh Acad. Sci. 46(1); 45-55: June 2022